Development of an evaluation framework for health information communication technology in contemporary pharmacy practice - Ayomide Ogundipe; Tin Fei Sim; Lynne Emmerton (Elsevier, 2023)
Background: Health information communication technology (ICT) has rapidly evolved in contemporary pharmacy practice worldwide. The Australian healthcare system is experiencing a paradigm shift to real-time interconnectivity for practitioners and consumers and interoperable digital health. With these developments come a need to evaluate use of technologies specifically in pharmacy practice to optimize their clinical functionality. There are no published frameworks for evaluating ICT needs or implementation in pharmacy practice. Objective: This paper proposes a theoretical framework for evaluating health ICT in pharmacy. Methods: Development of the evaluation framework was informed by a systematic scoping review and health informatics literature. Specifically, the framework drew upon critical appraisal and concept mapping of the TAM, ISS and HOT-fit validated models, with respect to health ICT in contemporary pharmacy practice. Results: The proposed model was named the Technology Evaluation Key (TEK). The TEK comprises of 10 domains; healthcare system, organization, practitioner, user interface, ICT, use, operational outcomes, system outcomes, clinical outcomes and timely access to care. Conclusions: This is the first published proposed evaluation framework developed for health ICT specifically in contemporary pharmacy practice. TEK represents a pragmatic way to ensure the development, refinement and implementation of new and existing technologies in contemporary pharmacy practice to keep pace with the clinical and professional requirements of community pharmacists. Operational, clinical and system outcomes should be evaluated as coexisting factors that may impact implementation. Validation research utilizing Design Science Research Methodology will enhance utility for end users and ensure the relevance and application of the TEK to contemporary pharmacy practice.